The therapeutic effectiveness of rational emotive therapy in improving assertive behavior in individual counseling - Pannathanath, Mathai (Animo Repository, 1989)
This study investigated the effectiveness of RET in assisting a college student. The client had difficulty in: (1) expressing his thoughts and feelings, (2) standing up for his rights/views, and (3) relating with people. This study employed the ABAB N of 1 or single case research design. The baseline behavior (A) was established three times: before, during and after the RET treatment. This was done by administering 16 PF and RAS tests. The treatment lasted for seven weeks with a break of two weeks in the middle. RET techniques such as disputing irrational beliefs, A-B-C theory of emotions, giving up self-rating, combating self-damnation, positive imagery and home works were employed to help the client. As a result of the therapy, the subject was able to discover his irrational beliefs. By discovering and disputing these irrational beliefs he was convinced that these can be replaced with rational ideas. The subject also recognized his rights as a person. He also learned to express his thoughts, feelings, and views. He was able to relate with people freely as equals. He was able to look and smile at people and talk in a normal voice without becoming nervous. He found it easier to make friends. Treatment was effective since criteria previously set were met. These were: 1. improvement in level of assertiveness as indicated by test scores 2. positive feedback of subject, his friends and perception of the therapist. Finally, the study recommends further exploration, in practice through research, the potential of RET technique.